INSIDE FINANCE CONSTRAINTS ON THE GROWTH OF ITALIAN SMALL MEDIUM SIZED ENTERPRISES - DONATI, Cristiana; CINQUEGRANA, Giuseppe; SARNO, Domenico (Theoretical and Practical Research in Economic Fields, 2012)
Our study confirms that the financial constraints of the small and medium size enterprises’ (SME’s) growth tend to appear as an excess of sensibility of the investment expenditures on the firm’s cash flow. Through the application of dynamic panel data techniques to an extended version of Eulero’s investment equation of a sample of Italian SMEs, the analysis shows that the growth of small firms subsample in backward regions of Italy is more constrained by inside finance than that of firms in more developed regions. This is because the typical information opacity of SMEs is worsened here by the unsatisfactory development of financial markets. Moreover our analysis ascertains that the small firms can significantly relax the constraints if they establish a close relationship with the banks, making it easier for the banks to access the firm’s information.